2020
DOI: 10.1097/mnm.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lutetium-177 tin colloid and Rhenium-188 tin colloid radiosynovectomy in chronic knee arthritis

Abstract: Objective To assess the role of Lutetium-177(Lu-177) tin colloid for radiosynovectomy and compare it with Rhenium-188 (Re-188) tin colloid radiosynovectomy for alleviation of pain in patients with chronic inflammatory arthritis of knee. Methods Patients of chronic inflammatory arthritis of the knee underwent pretherapeutic evaluation in a form of knee ultrasonogram, bone scan and clinical evaluation. Fifty-seven recruited patients were allocated at rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to the high interest in radiosynovectomy that has grown during the last decades, 188 Re application has been developed for managing several diseases [7]. The development of other radionucleotides persuaded a group of researchers to compare Re-188 and Lutetium-177; they reported that despite the good effects of Re-188, Lutetium-177 can be an appropriate alternative with more acceptable results for RA patients [13]. An investigation on the same population administered P-32 to their participating patients and demonstrated knee improvement [8] with similar results as those of the current study.…”
Section: Discussion_____________________________mentioning
confidence: 99%
“…According to the high interest in radiosynovectomy that has grown during the last decades, 188 Re application has been developed for managing several diseases [7]. The development of other radionucleotides persuaded a group of researchers to compare Re-188 and Lutetium-177; they reported that despite the good effects of Re-188, Lutetium-177 can be an appropriate alternative with more acceptable results for RA patients [13]. An investigation on the same population administered P-32 to their participating patients and demonstrated knee improvement [8] with similar results as those of the current study.…”
Section: Discussion_____________________________mentioning
confidence: 99%